PERFORMANCE OF THE THREE-ARMED UNSIGNALIZED INTERCHANGE ON JALAN TIPAR CAKUNG, EAST JAKARTA - Andika Setiawan; Harwidyo Eko Prasetyo; Heru Setiawan; Irnanda Satya Soerjatmodjo (International Journal of Civil Engineering and Infrastructure, 2022)
The growth of the population density greatly affects the level of transportation needs in the city of Jakarta. The increase in the number of vehicles that are lack of balanced with the development of infrastructure It will cause conflicts on the road, especially intersections. Therefore, it is necessary to conduct research on interchange to know the problems that occur. This research was conducted at the Tipar Cakung – Agung Sedayu interchange in East Jakarta with an observation time of 3 days. The method that used in this study is a field survey method, namely by collecting data on traffic. It carried out by recording the number of vehicles that pass through the intersection every 15 minutes. Then from the results of the survey and calculation with the analysis guided by Indonesian Road Capacity Manual (MKJI, 1997).  Based on the results of research for interchange performance in existing conditions, the highest traffic flow was obtained at 2831.7 pcu / hour, Degree of Saturation (DS) 1.05, delay on intersection (D) of 22.058 seconds/pcu and queue odds (QP%) in the range of values 44.93%-90.27%.